The role of submesoscale currents in structuring marine ecosystems. Issue 1 (December 2018) - Lévy, Marina; Franks, Peter; Smith, K.
Abstract From microbes to large predators, there is increasing evidence that marine life is shaped by short-lived submesoscales currents that are difficult to observe, model, and explain theoretically. Whether and how these intense three-dimensional currents structure the productivity and diversity of marine ecosystems is a subject of active debate. Our synthesis of observations and models suggests that the shallow penetration of submesoscale vertical currents might limit their impact on productivity, though ecological interactions at the submesoscale may be important in structuring oceanic biodiversity. Short-lived three-dimensional submesoscale currents, responsible for swirling ocean color chlorophyll filaments, have long been thought to affect productivity. Current research suggests they may not be effective in enhancing phytoplankton growth, but may have important contributions to biodiversity.